Immunotherapy for Food Allergy: Myth or Reality? - Soegiarto, Gatot (UI Scholars Hub, 2019)
Allergic reaction to food can have serious consequences. The only treatment option is strict allergen avoidance, but accidental ingestions happen frequently and can lead to severe and potentially life-threatening allergic reactions. Food allergy is one of the most common causes of anaphylactic reactions. Therefore self-injectable epinephrine should always be at hand in case of accidental exposure. Many food allergies may resolve over time, but most patients with persistent food allergies live with fear of anaphylactic reactions. Within the last several years, the usefulness of immunotherapy for food allergies has been investigated. Several food immunotherapies are being developed; which include oral, sublingual, epicutaneous, or subcutaneous administration. The approach follows the same principles as immunotherapy for other allergic disorders, consisted of an induction phase followed by a maintenance phase with regular intake of maximum tolerated amount of food. Although immunotherapy seems promising for food allergic patients, it remains an investigational treatment that need to be studied further before advancing into clinical practice. Hopefully, multicentre and randomizedcontrolled studies can provide answer to multiple questions including optimal dose, ideal duration of immunotherapy, degree of protection, efficacy for different ages, severity and type of food allergy responsive to treatment.